The Meaning of the Silent Treatment as Nonverbal Communication in Gen Z Romantic Relationship Conflicts - Salsabila Az-Zahra; Farida Nurfalah (Indonesian Journal Publisher, 2026)
Conflict in romantic relationships is an inevitable part of interpersonal communication. One common response to conflict in Generation Z romantic relationships is the silent treatment, a form of silence used to express emotions or withdraw from communication. Previous studies have primarily examined the silent treatment from a psychological perspective rather than as nonverbal communication in interpersonal relationships. This study aims to understand the meaning of the silent treatment as a form of nonverbal communication in Generation Z romantic relationship conflicts. Using a qualitative phenomenological approach, this study explored participants’ subjective experiences of the silent treatment. Six participants, consisting of three Generation Z couples, were selected through purposive sampling based on their experience with relationship conflicts involving the silent treatment. Data were collected through observation, documentation, and in-depth interviews, then analyzed using theories of nonverbal communication and interpersonal conflict. The findings show that the silent treatment is interpreted as a form of nonverbal communication used to express emotions, prevent conflict escalation, and create space for emotional regulation. It is reflected through avoiding eye contact, changes in facial expressions, silence during interactions, and reduced digital communication with partners. In all cases, the silent treatment was temporary and generally followed by reconciliation when communication resumed. These findings suggest that the silent treatment does not always have negative consequences but can also function as a strategy for emotional regulation and conflict management in Generation Z romantic relationships.